GEOGRAPHIC INFORMATION SYSTEM FOR SEARCHING HONDA MOTORCYCLE DEALERS IN MEDAN CITY USING A-STAR ALGORITHM - Pohan, Randy Novhendra; Fakhriza, M; Harahap, Aninda Muliani (ZERO: Jurnal Sains, Matematika dan Terapan, 2022)
Currently, motorbikes are a means of transportation that are often used by the community because they have advantages when compared to other means of transportation. One type of motorcycle that is widely used is a Honda motorcycle. Currently, there are many Honda motorcycle dealers spread across Indonesia, especially in Medan, but have not yet been integrated into a system, making it difficult for people who want to find such dealers. Another problem is that there is no map of the distribution of the nearest dealer from the community's location and there is no information about dealers covering products and ordering services online. With technology, the authors build a geographic information system with the A-Star algorithm that can assist in mapping dealer locations and can calculate the closest route that can be taken. This system is built based on Android using Kodular, Java and PHP programming languages, and uses Openstreetmap as a geographical map.